Author Correction: A detailed characterization of complex networks using Information Theory (Scientific Reports, (2019), 9, 1, (16689), 10.1038/s41598-019-53167-5) - CGS Freitas; ALL Aquino; HS Ramos; Alejandro Frery; OA Rosso (2021)
© 2021, The Author(s). An amendment to this paper has been published and can be accessed via a link at the top of the paper.